Hepatotoxicity during anti tuberculosis chemotherapy - Djebaili, R.; Guerza, O.; Romane, A. (International Journal of Medicine, 2024)
Introduction: Despite their efficacy in tuberculosis treatment, side-effects of anti-tuberculosis drugs can be serious or fatal. The aim of our study is to determine the prevalence of hepatic toxicities associated with anti-tuberculosis drugs, their evolutionary aspects, and their management.Patients and methods: A retrospective descriptive study including 82 patients having received antituberculosis treatment and who pre-sented a hepatic cytolysis, collected at the Tuberculosis and Respiratory Diseases Control Department of Batna- Algeria between 2016 -2023. The aim of our study is to determine the prevalence of hepatic toxicities of anti-tuberculosis drugs, their evolutionary aspects, as well as the modalities of their management.Results: 82 out of 119 (69.23%) patients who experienced other adverse events were recruited between 2016 and 2023, aged between 15 and 86 years, with an average age of 43 years and a female predominance of 63.41%. Cholestasis syndrome was noted in 21 patients and frank jaundice in 4. Cytolysis was discovered incidentally in 68% of patients; it was mild in 56 (68.29%), moderate in 16 (19.51%) and severe in 10 (12.19%). Transaminase disturbance appeared within 3 months in 76.82% of cases, whereas a delay of 30 days was noted for normalisation of the liver function test after cessation of anti-tuberculosis treatment in 62 (76%) patients. Definitive discontin-uation of isoniazid (INH) was adopted in 17 (20%) patients, while a reduction in the doses of rifampicin and isoniazid was decided in 65 (80%) patients.Conclusion: Drug-induced hepatitis is one of the major side-effects of anti-tuberculosis drugs and can be lethal, hence the need for rapid and appropriate management. Healthcare professionals need to be informed about the types of suspected adverse drug reactions, they should report in subjects at risk.